Weight loss - "Chatterjee, Upmanyu" (New Delhi, 2006)
Innocent and unremarkable, but for his near crippling obsession with sex and running, Bhola goes through life falling for the wrong people. When he marries and becomes a father, Bhola believes he has come close to achieving balance in his chaotic life. Until suddenly his past catches up with him and threatens to destroy his happiness.
Keywords: English fiction